TI_GERICHTE 12.2021.37 vom 6. August 2021 , Società a garanzia limitata - cessione di quote sociali - mantello d'azioni - TI Tribunale d'appello (2021)
Società a garanzia limitata - cessione di quote sociali - mantello d'azioni